Improving Public Procurement Outcomes : Review of Tools and the State of the Evidence Base - Fazekas, Mihály; Blum, Jurgen Rene (World Bank, Washington, DC, 2021)
Considering that about 15 percent of global gross domestic product flows through public procurement systems, the lack of systematic evidence on what works in this field is a major challenge for effective policy making. Hence, this paper systematically reviews the state of the evidence on major public procurement reforms and their impact on value for money and open access to public tenders. It discusses the reliably identified costs and benefits and systematically evaluates the quality of the evidence base, relying on academic and policy literature. The quality of evidence on the impact of public procurement interventions is mediocre, with reliable evidence established in multiple countries using diverse analytical methods only for selective, typically narrow tools. Although there is a range of policy tools with global policy interest and extensive implementation record, these have received little to no evaluation. As high-quality research uses different outcome measures, comparing intervention effectiveness is only possible for a very narrow outcome: savings. Comparing intervention types according to their effects on savings, centralized procurement and framework agreements stand out with the largest effects, over 50 percent. Most other intervention types were documented to achieve about 5-10 percent price savings if they were well implemented. Given the estimated US$11 trillion spent on procurement annually around the world, even savings of 1 percent amounts to US$110 billion annually. This systematic review points out that research on e-procurement and its variants, transparency portals, civil society supervision, and opening up the black box of public management, among others, would deserve considerably more research going forward.